Oligarquias, organização e governo: trajetórias de sobrevivência das elites partidárias no Brasil (1998-2018) - Assis, Pedro Paulo de (2021)
The process of oligarchization does not end with the emergence of the ruling elites – the rise to the top of the party does not guarantee dominance over the organization. If there is an explanatory mechanism that clarifies the aetiology of intra-party leadership (Michels, 2001), a thesis about the causes and origins of the phenomenon, there is also, even if still unexplored, a mechanism that explains the physiology of an organization dominated by ruling elites. A thesis on the functioning and maintenance of a party dominated by leaders. The emphasis is in the explanatory mechanism between organizational agents and party structures that continuously sustains the survival of these elites. We try to approach this unknown mechanism employing as an object the four largest national party organizations in the current Brazilian scenario (PFL-DEM, PMDB, PSDB, and PT, from 1998 to 2018). The main hypothesis of this study points out that, to survive, ruling elites restrict the level of intra-party competitiveness by concentrating control over certain strategic positions and resources of power in the governmental and organizational arenas. The results show that different configurations of surviving elites require distinct repertoires of organizational and governmental activities, restricting competitiveness in intra-party systems in singular ways. That is, the plural profiles of Brazilian ruling elites establish different types of resources and positions of power in the party arenas at different levels. The survival mechanism is shared by the organizations studied, but it manifests itself in unique ways. The four major Brazilian parties have important uniquenesses in the development of their oligarchy processes: they display certain profiles of turnover; they vary considerably in the forms of distribution of incentives in their bases, and they differ in the types of resources and positions of power that unbalance intra-party authority relations in favour of their elites. In addition, gathered and compared, the evidence indicates the need for dynamic coordination in conducting these repertoires of party activities to support leadership. The survival of elites (through a process of hegemonization or resistance) is also associated with adjustments in the distribution of organizational and governmental incentives, given the swaying in the competitive performance of each party and the progression of elite turnover. The specialized repertoires of activities are constantly adapting. The phenomenon of elite survival, due to the restriction of intra-party competitiveness, is a continuous process of incremental changes. The thesis is divided into two parts. Part I has three chapters, working on three connected objectives. In Chapter 1, we seek to understand the scope and limitations of Michels' (2001) classic Iron Law of Oligarchy – oligarchization as an intra-party process, whose outcome is the emergence of ruling elites. In Chapter 2, we seek to adapt the Michelsian theoretical framework to address the phenomenon of the survival of ruling elites. We discuss[ed] the dynamics that would follow the Iron Law, developing an approach capable of facing oligarchization as a continuous process (beyond the aetiology of the bosses) and a systemic process (involving arenas external to the organization). Closing Part I, in Chapter 3, we deal with research design specifications to map the surviving leaders and observe the different manifestations of the survival mechanism articulated in the four Brazilian party organizations (PFL-DEM, PMDB, PSDB and PT) in the last decades (from 1998 to 2018). Part II of the thesis has three analytical chapters. In Chapter 4, we survey the turnover profiles of the surviving ruling elites of the PFL-DEM, PMDB, PSDB and PT – their trajectories at the summits in terms of cartelization and territorial decentralization. We examined the developments of competition between leaders seeking positions in their National Executive Committees: the stages of survival of the ruling elites in each organization and the respective hegemonization and resistance movements over their intra-party systems in the analyzed period. In Chapter 5, we investigate the selective articulation of the structures of party activities in the organization and in the government by the ruling elites. We scrutinized the dynamics of relative concentrations between the party bases of the distribution of power positions and resources, associating the alignments of such allocations with the particular profiles of dominant party elites in each organization. Finally, in Chapter 6, we summarize the organizational and governmental repertoires built by the leaders to enable the course of their described survival trajectories. We highlight and contrast the dynamics of distribution and redistribution of power positions and resources dominated and allocated by the ruling elites at their bases. We focus on the different balance points reached in the oligarchization processes of the PFL-DEM, PMDB, PSDB, and PT – the unique manifestations of their shared survival mechanism.